2014
DOI: 10.14309/crj.2014.43
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Presentation of Splenic Rupture After Endoscopy in a Patient With Hemophilia A: Case Report and Review of the Literature

Abstract: An 88-year-old female presented with dyspnea on exertion and severe anemia. Colonoscopy was unremarkable and the patient was transfused with packed red blood cells prior to discharge. The patient returned 2 weeks later with severe abdominal pain, hypotension, and anemia. Computed tomography revealed splenic hematoma and hemoperitoneum. She bled from the surgical sites during emergent splenectomy and work-up revealed hemophilia A. We present, to our knowledge, a case of the longest reported delay in presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…It has been suggested that bowing of the endoscope along the greater curvature of the stomach can cause avulsion of the splenic or short gastric vessels. The strain can be so great as to tear the splenic capsule, and may be magnified by insufflation of the stomach [2,3,6,7]. Direct splenic injury can also result from manipulation of the endoscope, especially when larger caliber scopes such as the Olympus GF-UM3 and TJFV10 are utilized [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that bowing of the endoscope along the greater curvature of the stomach can cause avulsion of the splenic or short gastric vessels. The strain can be so great as to tear the splenic capsule, and may be magnified by insufflation of the stomach [2,3,6,7]. Direct splenic injury can also result from manipulation of the endoscope, especially when larger caliber scopes such as the Olympus GF-UM3 and TJFV10 are utilized [2].…”
Section: Discussionmentioning
confidence: 99%
“…Though many commonly acknowledged adverse events such as difficulty swallowing and abdominal discomfort are typically mild, splenic injury is an exceedingly rare and serious complication. While iatrogenic endoscopic splenic injury has been infrequently described following endoscopic retrograde cholangiopancreatography (ERCP) and colonoscopy, only a few reported cases have been attributed to EGD [1][2][3][4]. Sharp abdominal pain, hemodynamic instability, and signs of occult hemorrhage can indicate splenic rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with splenic injury present within 24 hours after procedure [ 1 12 ]. However, some patients may present 10 to 14 days after procedure [ 2 , 7 , 13 , 14 ] with the longest time reported from procedure to presentation being two weeks [ 2 ]. Left upper quadrant abdominal pain is the most commonly reported presenting symptom [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, patients may be completely asymptomatic [ 6 , 7 ]. Clinical signs of hypotension, anemia, and elevated white blood cell count may be present [ 2 , 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation